The Impact of Malaria in Pregnancy on Infant Susceptibility to Malaria Infection - Ratni Indrawanti; Mahardika Wijayanti; Mochamad Hakimi; Mohammad Juffrie; Enny Kenangalem; Faustina Helena Burdam; Leily Triyanti; Rintis Noviyanti; Din Syafruddin; Rukhsana Ahmed; Feiko ter Kuile; Jeanne Rini Poespoprojo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Malaria infection during pregnancy is a significant global health problem with substantialrisks for pregnant women, her foetus, and the newborn child. Infant malaria is a majorpublic health concern in Timika, Papua. The aim of the study was to investigate the impactof malaria during pregnancy on infant’s susceptibility to malaria infections, the timing ofits occurrence, the number of malaria infections during pregnancy. This was a cohortprospective study conducted in Timika, Papua from October 2013 to September 2016.Malaria investigation was done by microscopic and PCR methods. Demographic data andmalaria status of mother-infant pairs were collected and analyzed by SPSS 22.0 version.One hundred seventy-eight infants consisting of 95 (53.37%) infants born to motherswith malaria and 83 (46.63%) without malaria 91 (51.12%) boys and 87 (48.88%) girlswere involved in the study. The mean of mothers’ ages were 25.35 ± 6.30 vs. 26.0 ±5.69 years. At the ages of 6 and 12 months, infants born to malaria positive motherswere more susceptible to malaria infections compared to infants born to malaria negativemothers with RR = 3.49; 95%CI: 1.02-11.96; p = 0.03 and RR = 8.74; 95%CI: 1.14-66.81; p = 0.01, respectively. Independent risk factors of infant susceptibility to malariainfection during the first year of life were malaria in pregnancy (MiP) in 2nd trimester (RR= 4.50; 95%CI: 1.5-13.49; p = 0.07), pregnant women who only got malaria infection1 time during pregnancy (RR=2.95; 95%CI: 1.04-8.33; p = 0.04), and Papuan ethnicity(RR=3.58; 95%CI: 1.22-10.59; p = 0.02). In conclusion, infant susceptibility to malariais associated with maternal malaria status during pregnancy. MiP in second trimester,pregnant women who only had malaria once and Papuan ethnicity were independent riskfactors for infant’s increased susceptibility to malaria infection.